2018
DOI: 10.17269/s41997-018-0056-3
|View full text |Cite
|
Sign up to set email alerts
|

Domestic/intimate partner violence in the lives of immigrant women: a New Brunswick response

Abstract: Acknowledgement and better understanding of the cultural differences between service providers and immigrant survivors of D/IPV would go a long way to improve trust and break down barriers in communication. Revision of the New Brunswick Woman Abuse Protocols will highlight the perspectives of immigrant women. Long-term and increased funding for D/IPV and settlement public services will ensure that women-centered programming and professional translation services are available and improved collaboration takes pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…Research shows, however, that the risk for ongoing violence and lethality continues and often escalates after the relationship ends (Dawson, 2017; Office of the Chief Coroner for Ontario, 2019). Newcomer women's experiences of help-seeking and reasons for delaying seeking help after IPV also may be influenced by cultural/religious barriers, socio-economic challenges, socio-demographic factors (e.g., race, class, and age), legal factors, a lack of knowledge regarding available resources (Ahmad et al, 2009; Aujla, 2013, 2021; Barrett & St. Pierre, 2011; Chan, 2020; Guruge et al, 2019; Hyman et al, 2006; Okeke-Ihejirika et al, 2020), challenges related to language ability (Alaggia et al, 2017; Aujla, 2010; Guruge et al, 2019; Holtmann & Rickards, 2018), and loss of social support after migration (Ahmad et al, 2009; Guruge & Humphreys, 2009). Recent Canadian research has also indicated that current policies and support services are not adequately meeting the needs of newcomer women who have experienced IPV (Aujla, 2021; Okeke-Ihejirika et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research shows, however, that the risk for ongoing violence and lethality continues and often escalates after the relationship ends (Dawson, 2017; Office of the Chief Coroner for Ontario, 2019). Newcomer women's experiences of help-seeking and reasons for delaying seeking help after IPV also may be influenced by cultural/religious barriers, socio-economic challenges, socio-demographic factors (e.g., race, class, and age), legal factors, a lack of knowledge regarding available resources (Ahmad et al, 2009; Aujla, 2013, 2021; Barrett & St. Pierre, 2011; Chan, 2020; Guruge et al, 2019; Hyman et al, 2006; Okeke-Ihejirika et al, 2020), challenges related to language ability (Alaggia et al, 2017; Aujla, 2010; Guruge et al, 2019; Holtmann & Rickards, 2018), and loss of social support after migration (Ahmad et al, 2009; Guruge & Humphreys, 2009). Recent Canadian research has also indicated that current policies and support services are not adequately meeting the needs of newcomer women who have experienced IPV (Aujla, 2021; Okeke-Ihejirika et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They include income status, employment conditions, social and living conditions, racial/ethnic minority status, immigration status, cultural identity, sexual orientation, gender identity and/or disability. 23 Thus, overlooking these intersecting circumstances, in conjunction with a medical, psychiatric model of trauma and mental health, results in many psychotherapeutic modalities failing to provide context-informed services for survivors of Open access violence. 12 That is, the mental health outcomes of violence (particularly PTSD) are often taken as directly created by the experiences of violence itself, without consideration of how different individuals, depending on their social locations, react differently to violence and what diverse needs they have for trauma recovery.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“… 14 22 Social determinants of health address broader social and economic circumstances that determine the health of individuals and communities. 23 These circumstances mainly shape the availability and accessibility of resources and services for individuals and communities. They include income status, employment conditions, social and living conditions, racial/ethnic minority status, immigration status, cultural identity, sexual orientation, gender identity and/or disability.…”
Section: Introductionmentioning
confidence: 99%
“…The social determinants of health (SDH) “are the economic and social conditions that shape the heath of individuals, communities and jurisdictions as a whole” and SDH reflect the quality of resources made available by society to its members 12 . They help to predict outcomes, identify vulnerabilities, and provide a starting point for addressing health as a social concept 13 .…”
Section: Introductionmentioning
confidence: 99%